Watching for life - Zieroth, David, 1946- (Hugh MacLennan poetry series., 2022)
"From a balcony overlooking an urban back lane, a poet watches those walking below - their identities unknown and yet grasped through real and imagined evidence of foibles and personal inclinations, details of habit that reflect the strangers' inner selves, humanity in all its weaknesses, illnesses, and propensities. In watching for life David Zieroth ponders questions about how to live and how to continue. The poems reach out in imagining the lives of others, and the poet himself is watched in turn. Zieroth conjures the history of his environment and the people who pass through it, reminding us of "the place we occupy / unfinished within ourselves" and our hunger to locate ourselves in the strangers we encounter. Intimate and observant, watching for life features poetic reflections on men, women, children, crows and gulls, pigeons, rain and snow, patched pavement, delivery trucks, night, and time."--